3-Amino-1H-pyrazol-2-ium trifluoroacetate - Yamuna, T. S. (International Union of Crystallography, 2013)
The asymmetric unit of the title salt, C(3)H(6)N(3) (+)·C(2)F(3)O(2) (−), contains two independent 3-aminopyrazolium cations and two independent trifluoroacetate anions. The F atoms of both anions were refined as disordered over two sets of sites, with common occupancy ratios of 0.639 (12):0.361 (12). In the crystal, the cations and anions are linked via N—H⋯O hydrogen bonds, forming chains along [100] and [010].